Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Electronically and catalytically functional carbon cloth as a permeable and flexible counter electrode for dye sensitized solar cell - Tathavadekar, Mukta; Biswal, Mandakini; Agarkar, Shruti A.; Giribabu, Lingamallu; Ogale, Satishchandra (Electrochimica Acta, 2014)
In this work we demonstrate that a conducting carbon cloth obtained by one-step pyrolysis of easily available cellulose fabric competes favorably with the commonly employed expensive platinum/FTO system as a counter electrode for dye sensitized solar cell (DSSC). In view of the low carbonization temperature (1000 degrees C) which forbids full graphitization, the nature of carbon in this case is represented by topologically randomly assembled nanoscale graphene units (turbostratic carbon). This morphology has high density of edge states and oxygen containing surface groups rendering multitude of catalytic sites for the reduction of I-3(-). Moreover the cloth is permeable to the dye and/or liquid electrolyte and its absorption properties also help retain the electrolyte. A fairly high efficiency of 5.8% is achieved using such cloth as a counter electrode as against 7% with the conventional Pt/FTO system. Moreover, the permeable property of the cloth eliminates a complete step of drilling hard TCO substrates for final dispensing of electrolyte into the device and the sealing process is also facile. In fact even the dye can be dispensed through the cloth. Finally, the flexibility of the carbon cloth can adapt easily to flexible/wearable DSSC designs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: conducting carbon cloth; counter electrode; DSSC; without drilling

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads